Development of Learning Media for the Katapel Quiz Application on the Concept of Energy in Living Systems - Sridiyanti S. Dunggio; Tirtawaty Abdjul; Citron S. Payu; Masrid Pikoli; Ritin Uloli; Abdul Haris Odja (Jurnal Penelitian Pendidikan IPA, 2024)
This research aims to produce a product and describe the validity, practicality, and effectiveness of the Katapel quiz application learning media on energy in living systems. The research method used is Research and Development (R&D) research and uses the 4D development model. The research target was class VII of SMP Negeri 1 Asparaga, involving 22 students. The results of Katapel quiz application consist of validity obtained 3.73 in the "valid" category; practicality obtained 85.71% in the "Very Good" category, and through student response questionnaires, which received 88.59% in the "Very Good" category; the effectiveness obtained 84.42% in the "Good" category and through learning outcomes tests of students who obtained a pretest score of 39.09% and a posttest of 90.55% with an N-Gain of 0.84 in the "high" category. The research results concluded that the learning media for the Katapel quiz application had met the valid, practical, and effective criteria for improving student learning outcomes on the subject of Energy in Living Systems.